EFEK MEROKOK TERHADAP STATUS pH DAN VOLUME SALIVA PADA LAKI-LAKI USIA DEWASA DAN USIA LANJUT: EFFECTS OF SMOKING ON THE SALIVARY pH AND VOLUME IN ADULTS AND ELDERLY MALES - Tri Ayu Hidayani; Juni Handajani (TALENTA, 2010)
The nicotine in the cigarette affects the sympathetic and parasympathetic nerves. Smoking causes heat in oral mucose.This study aimed to evaluate the effects the smoking to salivary pH and volume among the young adults and elderlymales. Forty males were as subjects with approval of ethical clearance from Ethic Committee Medical Faculty ofYogyakarta Muhammadiyah University, Yogyakarta Indonesia. The subjects were divided into four groups, i.e. 10smoker adults (18 – 40 years) and 10 elderly (>60 years). The controlled subjects consisted of 10 non smoker adults (18 –40 years) and 10 elderly non smokers (>60 years). The subjects were instructed to gargle mineral water for one minutebefore collecting sample. The saliva samples were collected in the morning, around 60 minutes after smoking usingunstimulated method. The pH meter was used to measure salivary pH and the volume by using injection. Analysis datafor the salivary volume and pH was compared using unpaired t-test (p<0.05). The results showed that the salivary pH andvolume in elderly smokers were lower than adult smokers. In conclusion, smoking could not affect on the salivary pH andvolume in adults, and the salivary volume in elderly, but it can decrease the salivary pH in elderly.